Respuesta :

Answer:

The Answer is D

Step-by-step explanation:

All you do is add both equations 3^x+10x+2x-4

then you add the like varibles which is 10x+2x=12x

So, the answer is 3^x+12x-4

Answer:

The value of the function  (f + g)(x) is [tex]3^{x}+12x -4[/tex].

Option (D) is correct .

Step-by-step explanation:

As given the equation in the question be as follow.

[tex]f(x) = 3^{x} + 10x[/tex]

g(x) = 2x - 4

Thus

(f + g)(x) = f(x) + g(x)

[tex](f + g)(x)= 3^{x}+10x +2x -4[/tex]

Simplify the above

[tex](f + g)(x)= 3^{x}+12x -4[/tex]

Therefore the value of the function  (f + g)(x) is [tex]3^{x}+12x -4[/tex].

Option (D) is correct .